Restructuring World Politics : Transnational Social Movements, Networks, And Norms - Sikkink, Kathryn, 1955-; Riker, James V.; Khagram, Sanjeev (Book collections on Project MUSE., 2002)
A comprehensive look at the global movements that are transforming international relations.